Answer:
and ![y=-1](https://tex.z-dn.net/?f=y%3D-1)
Step-by-step explanation:
If two equations are given, we can solve one of the equation in terms of single variable and put it in the other equation which will further give the value of x and y.
For the given equations:
Equation:1
Equation:2
Solving equation multiply equation 2 with 4 on both the sides
Equation 3
Subtracting Equation:3 from Equation:1
![8x-5y-(8x+36y)=21-(-20)\\8x-5y-8x-36y=21+20\\-41y=41\\y=-1](https://tex.z-dn.net/?f=8x-5y-%288x%2B36y%29%3D21-%28-20%29%5C%5C8x-5y-8x-36y%3D21%2B20%5C%5C-41y%3D41%5C%5Cy%3D-1)
Putting value of 'y' in Equation:2 which will give the value of x
![2x+9y=-5\\2x+9(-1)=-5\\2x-9=-5\\2x=4\\x=2](https://tex.z-dn.net/?f=2x%2B9y%3D-5%5C%5C2x%2B9%28-1%29%3D-5%5C%5C2x-9%3D-5%5C%5C2x%3D4%5C%5Cx%3D2)
-3a+3a+6=7
0a=1
a=error. As a result, this equation has 0 solution. Hope it help!
X^2-2x=-8 add 1 to both sides
x^2-2x+1=-7 now the left side is a perfect square
(x-1)^2=-7 take the square root of both sides
x-1=±√-7 add 1 to both sides
x=1±√-7 which is
x=1±i√7 so
x=1+i√7 and 1-i√7
Answer:
-3 and infinity
Step-by-step explanation: